IMPLEMENTASI KOMUNIKASI TERAPEUTIK DALAM KEGIATAN KHITABAH - Sabari (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2020)
This study aims to how to apply the dimensions of therapeutic communication in preaching activities. The result of this research is that therapeutic communication which is often practiced in the world of health in the dimension of its action always contributes effectively in healing patients, so that it is not impossible if the therapeutic communication is also applied in preaching activities considering the complexity of life problems faced by people humans today. After trying to examine or examine the application of therapeutic communication in khitabah activities, it turns out that it is also very effective and has such a powerful effect on mad'u da'wah. The conclusions of this study include: first, the dimension of action in therapeutic communication has various stages. The stages are confrontation, immediacy, self-disclosure, emotional catharsis, and role playing. Second, the implications of the action dimension in khitabah activities can also be applied when dealing with audiences or mad'u with applied theory from the action dimension so that the stages are also the same as the action dimension in therapeutic communication but are adopted to solve problems related to social problems that occur among people.